Iatrogenic Insertion of Chest Tube inside the Right Pulmonary Artery: Unique, Unheard Complication, and Management - Arun Kumar Haridas; Arpan Shah; Umang Shah; Chandrakant Shah; Jayesh Rajpura (Journal of Medical Sciences and Health, 2021)
A 75-year-old male patient referred from a medical college for emergency surgical removal of chest tube from the right pulmonary artery, inserted while treating a right-sided pneumothorax. The patient was a known case of COVID pneumonia treated successfully, 2 months back. The patient developed sudden breathlessness and chest pain with saturation of 70%. The patient had gone to nearest medical college for evaluation. Chest X-ray showed right-sided pneumothorax. Chest physician inserted intercostal chest tube. After insertion of chest tube, the patient drained 1500 ml of frank blood. Chest tube clamped and referred to a tertiary care center. Emergency computed tomography (CT) pulmonary angiogram is done. It showed chest tube tip in the right pulmonary artery. In view of post-COVID, severe interstitial lung disease, patient was not suitable for open heart surgery with the support of heart-lung machine. The patient was stable when we were received; saturation was 90% with 5 L oxygen. CT chest showed diffuse fibrosis and resolving pneumonia. Echo showed severe pulmonary arterial hypertension. We did high-risk off- pump right thoracotomy and removed chest tube without much loss of blood. The injured right pulmonary artery repaired. Post-operative period was free of events and discharged successfully. In complicated cases, preferably thoracic surgeon and a well-trained, experienced chest physician should insert chest tube to avoid life-threatening complications.